2018
DOI: 10.1002/mbo3.731
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics of the Komagataeibacter strains—Efficient bionanocellulose producers

Abstract: Komagataeibacter species are well‐recognized bionanocellulose ( BNC ) producers. This bacterial genus, formerly assigned to Gluconacetobacter , is known for its phenotypic diversity manifested by strain‐dependent carbon source preference, BNC production rate, pellicle structure, and strain stability. Here, we performed a comparative study of nineteen Komagataeibacter genomes, three of which were newly contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 139 publications
(219 reference statements)
4
65
0
Order By: Relevance
“…It seems that the same Komagataeibacter species are not necessarily grouped together, as observed in this study. Consistently, in a recent study, K. xylinus NBRC 13693 was grouped with Komagataeibacter oboediens 174Bp2 rather than another same species K. xylinus E25, K. xylinus E26, and K. xylinus BCRC 12334 according to a clustering analysis of 868 orthologous proteins shared by 20 Komagataeibacter species (Ryngajłło, Kubiak, Jędrzejczak‐Krzepkowska, Jacek, & Bielecki, ). When the name Komagataeibacter was recently suggested as a new genus (Yamada et al, ), 16S rRNA gene sequence‐based phylogenetic and phenotypic characteristics were considered that could differentiate the Komagataeibacter species from other Gluconacetobacter species, but they were probably not specific enough to differentiate species within the Komagataeibacter genus.…”
Section: Resultssupporting
confidence: 71%
“…It seems that the same Komagataeibacter species are not necessarily grouped together, as observed in this study. Consistently, in a recent study, K. xylinus NBRC 13693 was grouped with Komagataeibacter oboediens 174Bp2 rather than another same species K. xylinus E25, K. xylinus E26, and K. xylinus BCRC 12334 according to a clustering analysis of 868 orthologous proteins shared by 20 Komagataeibacter species (Ryngajłło, Kubiak, Jędrzejczak‐Krzepkowska, Jacek, & Bielecki, ). When the name Komagataeibacter was recently suggested as a new genus (Yamada et al, ), 16S rRNA gene sequence‐based phylogenetic and phenotypic characteristics were considered that could differentiate the Komagataeibacter species from other Gluconacetobacter species, but they were probably not specific enough to differentiate species within the Komagataeibacter genus.…”
Section: Resultssupporting
confidence: 71%
“…() and Ryngajłło et al . (). This fact suggests that these strains could be taxonomically assigned to the Komagataeibacter genus instead of the Gluconacetobacter .…”
Section: Resultsmentioning
confidence: 97%
“…In this sense, the diversity in the regulatory network of cellulose biosynthesis has been discussed by Ryngajllo et al . for Komagataiebacter strains (Ryngajłło et al ., ), and we cannot exclude that these operons might be active under other environmental growth conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, comparative genomic and transcriptomic analyses are gaining attention in the scientific community. Recently, it has been shown that high complexity of regulatory mechanisms, directly or indirectly involved in the cellulose biosynthesis in Komagataeibacter strains, could be predicted by comparative genomic analysis (Ryngajłło et al ., ). Transcriptome analysis‐based RNA‐seq is an important technique to identify differentially expressed genes under distinct experimental conditions in bacteria.…”
Section: Perspectivesmentioning
confidence: 97%